Study on red blood cell alloantibodies detection in malay women during pregnancy - Shah Reza, Johan Noor (Pusat Pengajian Sains Perubatan, 2013)
Pregnancy is known to cause red blood cell (RBC) alloimmunisation which may lead to the production of harmful alloantibodies and subsequently potentially to cause haemolytic disease of fetal and newborn (HDFN). However, RBC alloantibodies are significantly different between different populations and ethnics. Aim of this study is to determine the prevalence of RBC alloantibody among Malay pregnant women and its association with HDFN. Clinical and serological data of 5163 Malay pregnant women who attended labour room, Hospital Universiti Sains Malaysia were collected and analyzed prospectively. The blood samples were subjected to standard blood bank procedure for antibody screening and identification. The infant of women with positive antibody screening was monitored for evidence ofHDFN. Fifty one (0.99%) pregnant women were found to have irregular RBC alloantibodies and when the specificities were further characterized, 30 (0.58%) women were found to possess clinically significant alloantibody. Most of the clinically significant alloantibodies belonged to Rhesus (Rh) system (55.8%) where anti-E (33.3%) was the most common antibody identified, followed by anti-D (10.0%). Fourteen (0.27%) infants were clinically considered to develop HDFN. Anti-D, anti-c and anti-K were identified to cause moderate to severe HDFN. In conclusion, prevalence of RBC alloantibody in Malay pregnant women is low (<1 %), which is similar to other published studies. There were differences in the distribution of alloantibody specificity, however the antibodies toward Rh antigen are still the commonest clinically significant alloantibody identified. Considering the low prevalence of clinically significant alloantibodies and HDFN, the value of current routine antenatal RBC antibody screening practice in most Western countries becomes questionable and may not be directly applicable to Malaysian community without modification. The antibody screen should be restricted to women who are RhD negative, or who have a history of HDFN especially due to anti-c and anti-K.